Characterization and Degradation of Masonry Mortar in Historic Brick Structures. (27th April 2014) - Brosnan, Denis A.
Abstract : This study characterized mortars from a masonry fortification in Charleston, South Carolina (USA), harbor where construction was during the period 1839–1860. This location for analysis was interesting because of the sea water impingement on the structure. The study was included as part of an overall structural assessment with restoration as an objective. The mortars were found to be cement, lime, and sand mixtures in proportions similar to ones expected from the historic literature, that is, one part binder to two parts of sand. The binder was found to be American natural cement, a substance analogous to the European Roman cement. The results suggest that the thermal history of the cement during manufacturing affected setting rate explaining why the cements were considered as variable during the mid-to-late 1800s. Fine pores were found in mortars exposed to sea water resulting from corrosion. Contemporary natural cement was shown to release calcium in aqueous solution. While this release of calcium is necessary for setting in natural and Portland cements, excessive calcium solution, as exacerbated by sea water contact and repointing with Portland cement mortars, was shown to result in brick scaling or decay through cryptoflorescence.